2011
DOI: 10.3945/ajcn.110.010132
|View full text |Cite
|
Sign up to set email alerts
|

Energy-balance studies reveal associations between gut microbes, caloric load, and nutrient absorption in humans

Abstract: These results show that the nutrient load is a key variable that can influence the gut (fecal) bacterial community structure over short time scales. Furthermore, the observed associations between gut microbes and nutrient absorption indicate a possible role of the human gut microbiota in the regulation of the nutrient harvest. This trial was registered at clinicaltrials.gov as NCT00414063.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
751
13
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,053 publications
(825 citation statements)
references
References 30 publications
39
751
13
22
Order By: Relevance
“…Nonetheless, analysis of chemical composition at the single-cell level confirmed that the overall cellular composition of bacteria within the abundant bacterial groups Bacteroidales and Lachnospiraceae was altered by HF feeding, which may be due to the shifting phylotype dynamics that were observed within this group and possibly also altered activity. While many studies have shown that microbial diversity is altered by dietary changes (Clavel et al, 2005;Martinez et al, 2009;Jumpertz et al, 2011;Kau et al, 2011), much less is known about the impact of diet on the metabolic potential of gut microbiota (Martin et al, 2010;McNulty et al, 2011;Muegge et al, 2011). To our knowledge, this is the first report on the adaptive response of the gut metaproteome to dietary challenge.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, analysis of chemical composition at the single-cell level confirmed that the overall cellular composition of bacteria within the abundant bacterial groups Bacteroidales and Lachnospiraceae was altered by HF feeding, which may be due to the shifting phylotype dynamics that were observed within this group and possibly also altered activity. While many studies have shown that microbial diversity is altered by dietary changes (Clavel et al, 2005;Martinez et al, 2009;Jumpertz et al, 2011;Kau et al, 2011), much less is known about the impact of diet on the metabolic potential of gut microbiota (Martin et al, 2010;McNulty et al, 2011;Muegge et al, 2011). To our knowledge, this is the first report on the adaptive response of the gut metaproteome to dietary challenge.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the quantitative contribution of the gut microbiota to host energy balance remains elusive. Jumpertz et al, (2011), recently proposed that an increased energy harvest of ca. 150 kcal is associated with an increase of 20% in the sequence occurrence of Firmicutes and a corresponding decrease in the Bacteroidetes in humans, although the impact of high inter-individual differences in the percentage of energy lost in stools have been discussed (Heymsfield and Pietrobelli, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a very recent report showed that short-term alterations in nutrient load induced rapid changes in the gut microbiota in lean, but not obese, humans ( 13 ). Specifi cally, in lean individuals, increases in nutrient load resulted in an increased relative abundance of Firmicutes (and a corresponding decrease in Bacteroidetes ) and increased energy harvest.…”
Section: © 2012 By the American College Of Gastroenterologymentioning
confidence: 99%
“…Increased lipogenesis and reduced FA oxidation result in increased susceptibility to hepatic steatosis and the subsequent consequences (63). Several studies indicated that an increase in the relative abundance of the members of Firmicutes, and especially of some Clostridium clusters, is involved in harvesting energy from the diet (17,18,64), and this contributes to the development of excessive weight gain and hepatic lipogenesis. With the use of germ-free animal models, it has been shown that the gut microbiota increases energy harvested from dietary polysaccharides and augments key enzymes in hepatic de novo FA biosynthesis, including acetyl-CoA carboxylase (ACC) and FA synthase (FAS), and consequently, hepatic TG accumulation.…”
Section: Introductionmentioning
confidence: 99%